2018
DOI: 10.18203/2319-2003.ijbcp20185166
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study on causality, severity and preventability assessment of adverse drug reactions in a tertiary care hospital in India

Abstract: Background: The present study was undertaken to evaluate the incidence and pattern of adverse drug reaction (ADRs), causality, severity and preventability of ADRs.Methods: Data was collected and analyzed with the information such as patients’ demographic details, associated co-morbid conditions and detailed drug related information gathered from ADR reporting forms. World Health Organization (WHO) scale was used for assessing causality, modified Hartwig scale was used for assessing severity and modified Schumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
2
2
0
Order By: Relevance
“…15 The present study was done to analyze the ICSR forms (n=382) collected from various departments, shows equal distribution of ADRs among both the genders. This was a comparable finding to that reported by Jose and Belhekar et al 15,16 However, the spontaneous reporting studies in our country had observed high percentage of ADRs in females. [17][18][19][20][21][22] The various factors influence the drug metabolism and response of individuals which include differences in body mass index, genetic constitution and differences in levels of various enzymes responsible for drug metabolism.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…15 The present study was done to analyze the ICSR forms (n=382) collected from various departments, shows equal distribution of ADRs among both the genders. This was a comparable finding to that reported by Jose and Belhekar et al 15,16 However, the spontaneous reporting studies in our country had observed high percentage of ADRs in females. [17][18][19][20][21][22] The various factors influence the drug metabolism and response of individuals which include differences in body mass index, genetic constitution and differences in levels of various enzymes responsible for drug metabolism.…”
Section: Discussionsupporting
confidence: 92%
“…23 In present study, 21.46% of ADRs were reported in age group of 40-49 years, 17.54% of ADRs were reported in age group 50-59 years and 19.12% of ADRs were reported in the elderly group. Since previous studies have stated that advanced age increases the risk of ADR due to pharmacokinetic and pharmacodynamics changes, the present study was comparable to the findings reported by Scheneiderjk, Belhekar, David, Ramesh, and Arulmani et al 6,[16][17][18][19]24,25 The seriousness criteria as observed in the present study is 27.2% (n=382). The present study reports of seriousness criteria were different from the studies reported by Singh, Venkatasubbaiah and Sneha et al which was 14.93% (n=154); 5.12% (n=254) and 39% (n=177) respectively.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Considering causality assessment our end result showed that 70% ADRs were probable and 30% were possible as per the WHO causality assessment scale which changed into contrary from the questionary primarily based totally Naranjo's algorithm, where 36% ADRs were probable and 64% were possible and additionally contrary to observe performed through Melo et al where 19.8% ADRs were probable and 67.4% were possible. According to Hartwig's severity scale, mild ADRs have been described as those which does not by itself require prolongation of hospitalization and could be managed by simple measures, moderate were those ADRs which needed prolongation of hospital stay of the patient for treatment of the same and severe were life-threatening ADRs [23].…”
Section: Resultsmentioning
confidence: 99%